Methodological guidelines for the scientific research of false reports on planted explosive devices in the Republic of Serbia - Mijalković, Saša; Milašinović, Srđan (Sociološki pregled, 2024)
During 2022 and 2023, Serbia was affected by a wave of false reports of planted explosive devices in public places (so-called “telephone terrorism”). In the public, it was sensationally presented as terrorism, cyber-terrorism, high-tech crime, letter-bombs, false reporting of a crime, endangering public order and peace, and special war, which contributed to the “nervousness” of citizens and the disruption of the usual lifestyle, as well as mistrust in the state power. Since “telephone terrorism” was not a subject of scientific interest in Serbia, since methodological dilemmas are evident when interpreting/ researching phenomena, since there are problems of distinguishing “telephone terrorism” from similar threats and there is an obvious conceptual-categorical chaos in this regard, a need arose to establish certain methodological guidelines for future researchers from the perspective of sociology of terrorism.
Keywords: terrorism; “telephone terrorism”; false reporting of planting explosive devices; methodology of scientific research; sociology of terrorism